Meningkatkan Pemikiran Kreatif Dengan Model Pembelajaran Project Based Learning Kelas V Mi Tarbiyatus Sibyan Kabupaten Probolinggo - Ani Anjarwati; Ajunaida Kurniawati; Farihah Zamili; Malqa Dewi Royyana; Hasyim Muzadi (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
From the results of observations at MI Tarbiyatus Sibyan found problems in learning, as evidenced by students' understanding of the material effect of air pollution on respiratory organs which is still low. The lack of learning media in the classroom is a very strong reason for this. And of course in this case it must be addressed immediately because it greatly affects student learning outcomes. One of the solutions for student learning problems is the teacher using the Project Based Learning (PjBL) learning model. This method is expected to have an impact on students to increase creativity and critical thinking. For this research method, researchers used quantitative descriptive and qualitative descriptive. Quantitative descriptive in this study is that for each cycle carried out the proportion of evaluation test results will be calculated, while qualitative description is information from the results of observation and elaboration in the form of explanations made by educators and students. From the results of the class action assessment (PTK) it was stated that the students' pretest scores were still said to be low, but after the presentation of material regarding the effects of air pollution on the respiratory organs and the posttest, the students' creative and critical thinking abilities experienced a fairly good increase.